Serum cell‐free DNA levels are a useful marker for extramammary Paget disease. (7th April 2019) - Mijiddorj, T.; Kajihara, I.; Tasaki, Y.; Otsuka‐Maeda, S.; Sakamoto, R.; Sawamura, S.; Kanazawa‐Yamada, S.; Egashira, S.; Inoue, K.; Makino, K.; Miyashita, A.; Aoi, J.; et al.
Summary: Background: Although carcinoembryonic antigen (CEA) and cytokeratin 19 fragment (CYFRA) are useful markers for extramammary Paget disease (EMPD), serum CEA and CYFRA levels are not elevated in most patients with EMPD without metastasis. Cell‐free (cf)DNA has attracted attention as an indicator of clinical conditions in several cancers. Objectives: To identify further useful biomarkers for the detection of EMPD, including early lesions, and to study the clinical implications of cfDNA in EMPD. Methods: cfDNA were isolated from serum of patients with EMPD with and without metastasis, and from healthy volunteers. Serum extracts were amplified using polymerase chain reaction. Results: Serum cfDNA levels were significantly elevated in patients with EMPD with or without metastasis compared with those in healthy controls. Serum cfDNA was a better diagnostic marker for the presence of EMPD than serum CYFRA. Moreover, the postoperative serum cfDNA levels were significantly lower than those from the preoperative samples, and the change in serum cfDNA levels reflected the clinical courses of patients with EMPD treated with chemotherapy. Conclusions: Taking the evidence together, serum cfDNA levels may be a useful marker for diagnosis and disease progression in EMPD. What's already known about this topic? Serum levels of carcinoembryonic antigen (CEA) and cytokeratin 19 fragment (CYFRA) are not elevated in most patients with extramammary Paget disease (EMPD) without metastasis. Cell‐free (cf)DNA has attracted attention as an indicator of clinical conditions in several cancers. There are few reports of the clinical implications of cfDNA in dermatology. What does this study add? Serum cfDNA levels were significantly elevated in patients with EMPD with or without metastasis compared with those in healthy controls. Postoperative serum cfDNA levels were significantly lower than those from the preoperative samples. Changes in serum cfDNA levels reflected the clinical courses of patients with EMPD treated with chemotherapy. What is the translational message? Serum cfDNA levels in patients with EMPD are a useful marker for the detection of EMPD, including localized EMPD. Changes in serum cfDNA levels in an individual patient may reflect the clinical course of EMPD. Abstract : Linked Comment : Ellis. Br J Dermatol 2019; 181 :439–440 . Respond to this article